A compendious method for the raising of the Italian brocoli ... as also an account of the la Lucerne ... and other grass-seeds. 5th ed., to which is added an account of the success of the burning of Clay etc (London, 1731)
With: A dissertation on the true cythisus of the ancients, by St. Switzer.